1997
DOI: 10.1016/s0014-2921(97)00063-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth effects of European integration

Abstract: This paper deals with the effects of European integration in the EC and EFTA on economic growth. Base regressions suggest that EC and EFTA memberships do in fact have a positive and significant effect on economic growth, and that there is no significant difference between EC and EFTA membership. This result is not completely robust with respect to changes in the set of control variables and to measurement errors. Nonetheless, the results suggest that regional integration may not only affect resource allocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(107 citation statements)
references
References 38 publications
(34 reference statements)
5
86
1
3
Order By: Relevance
“…On average for the whole EM-11 group, income convergence appears more likely as the projection year increases. This result is in line with the existing empirical results in the literature, which have consistently shown that income dynamics in Europe (and in the EU in particular) are consistent with the existence of convergence in income levels over time (see for example the results in Sala-i-Martin (1996), Henrekson et al (1997) or Crespo Cuaresma et al (2008)). The average results presented in Figure 2 hide a considerable amount of variation across countries in terms of income convergence dynamics in the projection years.…”
Section: Projection Results: Income Convergence Prospects In Europesupporting
confidence: 91%
“…On average for the whole EM-11 group, income convergence appears more likely as the projection year increases. This result is in line with the existing empirical results in the literature, which have consistently shown that income dynamics in Europe (and in the EU in particular) are consistent with the existence of convergence in income levels over time (see for example the results in Sala-i-Martin (1996), Henrekson et al (1997) or Crespo Cuaresma et al (2008)). The average results presented in Figure 2 hide a considerable amount of variation across countries in terms of income convergence dynamics in the projection years.…”
Section: Projection Results: Income Convergence Prospects In Europesupporting
confidence: 91%
“…Thus, the results obtained in Henrekson et al (1997) suggest that European integration may affect not only static efficiency through changes in resource allocation, but also long term growth rates.…”
Section: Review Of the Literature On European Convergencementioning
confidence: 89%
“…Edwards (1998) and Dollar (1992) find evidence for a positive impact of international trade on growth. Concerning the European integration, Henrekson et al (1997) find positive dynamic effects, while Vanhoudt (1999) rejects a positive impact on the growth rate. Badinger (2001) argues that the European integration has unfold a significant temporary growth effect.…”
Section: Introductionmentioning
confidence: 99%